Neutralizing antibody response to different COVID-19 vaccines in Brazil: the impact of previous infection and booster doses - Caetano, Beatriz L. L.; Pinto, Paolla B. A.; Pacheco, Agatha R.; Lage, Agnes R.; Pereira, Aline S. G.; Nascimento, Amanda V. P.; Machado, Thiago R.; Paulino, Anderson; Medeiros, Thiago L.; Fernandes-Siqueira, Lorena O.; Da Poian, Andrea T.; Horbach, Ingrid S.; et al. (Frontiers in Immunology, 2025)
IntroductionIn Brazil, three COVID-19 vaccines were among the first widely used (CoronaVac, ChAdOx1, and BNT162b2), which aimed to induce neutralizing antibodies (NAbs) against the original SARS-CoV-2 strain. Although effective against severe disease, they showed waning NAb levels and reduced efficacy against variants, prompting booster doses. Thus, it is important to investigate and compare the response induced by these vaccines and boosters.MethodsIn this study, we compare the magnitude, durability, and cross-reactivity of NAbs among vaccinated volunteers in Brazil using an enzyme-linked immunosorbent assay (ELISA)-based assay that measures Abs capable of blocking the interaction between the receptor binding domain (RBD) and human angiotensin-converting enzyme 2 (ACE2) receptor.ResultsThe BNT162b2 two-dose regimen resulted in the highest and most durable NAb levels, followed by ChAdOx1, while those induced by CoronaVac significantly declined over time. Breakthrough infections boosted NAb levels, especially for CoronaVac and ChAdOx1. All vaccines showed reduced neutralizing capacity against Gamma, Delta, and Omicron variants. Booster doses, particularly the first one, significantly increased and maintained NAb levels, including those against Omicron.DiscussionOur findings provide valuable population-based comparison of NAb levels elicited by different vaccines following primary inoculation and booster doses. Notably, the mRNA vaccine exhibited a strong primary and initial booster NAb response against SARS-CoV-2.